The Value Of Islamic Education Film “Imam Tanpa Makmum” In The 2023 - Siti Ruqoiyah; Emilie Dason; Nur Alfi Mua’nayah; Sigit Tri Utomo; Ana Sofiyatul Azizah; Gunarti Ika Pradewi (PT Mutiara Bustan Ilmu, 2025)
This study describes the value of Islamic education in the film Imam Tanpa Makmum, which includes the value of faith, the value of worship, and the value of morals. The purpose of this study is to find out how the storyline in the film Imam Tanpa Makmum contains Islamic educational values and what Islamic educational values are contained in the film Imam Tanpa Makmum. The method used is a qualitative research method, a narrative approach, and a type of library research or literature study. Data sources include primary data and secondary data; primary data comes from the film Imam Tanpa Makmum, and secondary data comes from journals, books, and the internet related to the research. Data collection techniques use observation and documentation techniques. The results of the study in the film Imam Tanpa Makmum show that the storyline contains Islamic educational values such as carrying out Allah's commands, obeying parents' commands, being polite, helping others, being grateful, honest, studying, giving alms, and visiting the sick. The Islamic education values contained include the value of faith (I'tiqodiyah), which is faith in Allah, faith in the Messenger, faith in the Last Day, and faith in qada and qadar. The value of worship (Amaliyah) found in the film Imam Tanpa Makmum is prayer and Umrah. Moral values (Khuluqiyah) include morals towards Allah, morals towards the Messenger, morals towards parents, and morals towards others.